2023
DOI: 10.1007/s00127-023-02446-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimated impact of the COVID-19 pandemic on the prevalence and treatment of depressive symptoms in Peru: an interrupted time series analysis in 2014–2021

Abstract: Purpose The COVID-19 pandemic increased the burden of mental disorders worldwide. Peru has been one of the countries most affected by COVID-19, however, studies evaluating the medium and long-term consequences of the pandemic on Peruvians’ mental health are recent and represent a new field of study in proliferation. We aimed to estimate the impact of the COVID-19 pandemic on the prevalence and treatment of depressive symptoms using nationally representative surveys in Peru. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…These findings suggest that, as a whole, that CMHCs managed to cope with the difficulties that the COVID-19 pandemic produced in mental health services. Our results are consistent with a population-based study that found a trend toward an increase in people with depressive symptoms in Peru who had access to treatment during the pandemic (Villarreal-Zegarra et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that, as a whole, that CMHCs managed to cope with the difficulties that the COVID-19 pandemic produced in mental health services. Our results are consistent with a population-based study that found a trend toward an increase in people with depressive symptoms in Peru who had access to treatment during the pandemic (Villarreal-Zegarra et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our study could provide a baseline estimate for pre-pandemic assessments. There is evidence that the prevalence and intensity of emotional problems in the population increased during the pandemic [ 77 ]. In addition, our results contribute to knowing the prevalence of BS by the subgroups already mentioned, data that are necessary for the design of public policies for the protection of occupational health (license for temporary disability) and the promotion of well-being, prioritizing certain regions, occupational groups, work areas and dimensions of BS, to control and reduce BS and improve the lifestyles of health professionals and the quality of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we can confirm a significant relationship between reassurance seeking behavior and depression, albeit with a small effect. It is important to address this issue because the prevalence of depression has increased sevenfold since the COVID-19 outbreak (Bueno-Notivol et al, 2021;Villarreal-Zegarra et al, 2023). 10.3389/fpsyg.2023 National, as well as international Public Health institutions are advised to address the state of general public mental health, in order to improve the wellbeing of citizens.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we can confirm a significant relationship between reassurance seeking behavior and depression, albeit with a small effect. It is important to address this issue because the prevalence of depression has increased sevenfold since the COVID-19 outbreak ( Bueno-Notivol et al, 2021 ; Villarreal-Zegarra et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%